STRATEGI PENGELOLAAN KAWASAN PESISIR KABUPATEN MERAUKE (Studi Kasus di Wilayah Pesisir Kawasan Ndalir, Kawasan Payumb dan Kawasan Lampu Satu, Distrik Merauke Kabupaten Merauke) - Irba Djaja (Universitas Musamus, Merauke, Papua, 2011)
This research aim to (1) find out the condition of coastal area of Merauke Regency, and (2) arrange the mangement strategy of coastal area of Merauke Regency. This research was carried out the coastal area of Merauke Regency. The method used was descriptive qualitative analysis. The primary data were obtained throught direct observation, interview, and questionnare, while the secondary data were collected through llibrary research and obtained from related institutions, goverment, and agencies. The suporting data were charts, general condition of research locations, weather, and other. A’WOT method which was the combination of AHP (analytical hierarchy process) and SWOT (strengths, weaknesses, opportunities, and threats) were used to determine alternative guidance of policy strategies. The results show that to achieve the management policy by Local Government of Merauke Regency has not shown result which are positive, haves the character of sectoral and less integrated. To reach management of going concern Merauke Regency coastal area, it is necessary to implementation strategy guidance involving on strategy that need to be done is the reinforcement of conservation program bases on public (0,70) the Improvement of stakeholders roles (0,65), the Improvement of participation of public in conservation of coastal area (0,60), the Improvement of quality of coastal area public SDM (0,50), the Improvement of enableness public economics around coastal area (0,45), and the Improvement of law and institution (0,40).